(3OQI GdCSdGc aj OhdI GdCJQGcs - (3GdMSf Hf YeQ Hf GdMSf Hf MHjH, CHh eMeO, HOQ GdOjf GdMdHj,J (B779 (3g` s
(3ChdgG (B:s
(3jHJOF ef SfI (B762(3g` s
(3BNQgG (B:s
(3jfJgi Edi SfI (B801(3g` s
(3Ke jdi Pdc JcedI dGHf GdeDda JfJgi SfI (B801 (3g`s
(3QGLY HbjI fSNI gPG GdcJGH ai GdbSe GdChd ef gPG GdagQSJ HQbe (B235s
(3YfGhjf GdJQGLe ehLhOI ai MhGT GdfSNIs
(3fSNI QGHYI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B208 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B206 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B169s
Keywords: (3GdJGQjNs